Brief Intervention Impact on Truant Youths' Marijuana Use: Eighteen-Month Follow-Up. Issue 1 (2nd January 2016) - Dembo, Richard; Briones-Robinson, Rhissa; Schmeidler, James; Wareham, Jennifer; Ungaro, Rocío; Winters, Ken C.; Karas, Lora; Wothke, Werner; Belenko, Steven
ABSTRACT: School truancy among teenagers remains a serious national problem, as evidenced by its significant association with school performance, psychological, and behavioral problems. Truancy is also positively associated with substance abuse. This study presents 18-month outcome data from a National Institute on Drug Abuse (NIDA)-funded controlled trial that examined the efficacy of a brief intervention (BI) to reduce marijuana use among truant youths. Adolescents and their parents were randomly assigned to receive either a two-session youth-only session (BI-Y), two-session youth and additional parent session (BI-YP), or standard truancy services (STS). Analyses of an auto-regressive lag model examined marijuana use at three months, six months, 12 m onths, and 18 m onths post-intervention. Results indicated adolescents receiving BI services, especially BI-Y services, showed significant reductions in marijuana use, at 18-month follow-up. BI-YP youths showed a greater increase in marijuana use than BI-Y youths. Reasons for this unexpected finding are discussed. Implications of the results for future research and service delivery also are discussed.